Uji efektivitas ekstrak etanol daun bayam hijau (Amaranthus hybridus L.) sebagai imunostimulan pada mencit putih jantan (Mus musculus) - Tarigan, Rida Evalina; Sinaga, Arinda Agnes; Shufyani, Fahma (Journal of Pharmaceutical and Sciences, 2025)
The immune system plays a critical role in defending the body against pathogens, and enhancing its activity through immunostimulants is essential for improving health. This study aims to evaluate the immunostimulatory potential of ethanol extract from green amaranth leaves (Amaranthus hybridus L.) in male white mice (Mus musculus). The ethanol extract green amaranth leaves was prepared from dried green amaranth leaves and tested for its effect on phagocytic activity using the carbon clearance method. Phytochemical screening revealed the presence of flavonoids, saponins, tannins, and steroids. The animals were divided into five groups: negative control (0.5% Na CMC), positive control (Stimuno Forte®), and three experimental groups receiving varying doses of the ethanol extract (125 mg/kg, 250 mg/kg, and 500 mg/kg body weight). The results indicated that the ethanol extract significantly enhanced phagocytic activity, with the most optimal effect observed at 125 mg/kg body weight. The stimulation index increased with higher doses, demonstrating the dose-dependent immunostimulatory effect. The study concludes that the ethanol extract of green amaranth leaves can serve as an effective natural immunostimulant, with the 125 mg/kg body weight dose being the most effective in enhancing immune function in male white mice. These findings suggest the potential of green amaranth as a therapeutic agent for immune-related disorders.